Least limiting water range and degree of compactness of soils under no- tillage - Lima, Claudia Liane (2015)
The least limiting water range (LLWR) and degree of compactness (DC) can be useful indicators of soil physical quality and crop yield. This study focused on assessing of LLWR, DC and evaluation of critical values to crop growth of an Alfisol and Oxisol under no-till management. Undisturbed soil cores were taken from the layer 0.00 - 0.20 m depth. Soil water retention curve, soil penetration resistance curve, air-filled porosity and bulk density (Bd) were measured. The range of LLWR variation was limited by volumetric water content at field capacity and penetration resistance. Values of LLWR varied from 0.00 - 0.14 m3 m-3 to Alfisol and 0.00 - 0.04 m3 m-3 to Oxisol. The critical values of the Bd and DC for crop development were 1.79 Mg m-3 and 1.35 Mg m-3 and 96% and 74% to Alfisol and Oxisol, respectively. Further researches relating LLWR, DC and crop response are still required in soils with different conditions and management.